The Role Of Ginger Administration Toward Oxidative Stress In Women’s Health Reproduction: A Literature Review - Yasmin, Riska; Pertiwi, Desi; Rahmawati, Rahmawati (Akademi Kebidanan Bunga Husada Samarinda, 2021)
Objectives This study as a system review was aimed to review the role of ginger administration in reducing oxidative stress level for women in their reproduction health. This was literature review to give further information about the role of ginger in reducing oxidative stress condition and was written with the help from secondary data analysis such as databases, various journals, books, articles and key wordsResult Ginger could be one of the alternative medicine to treat reproductive problems like PCOS, help the implantation process in the uterus, normalized estrogen and progesterone imbalance, reduce cortisol level which can affect women fertility, and help womento deal with premenstrual syndromeConclusion Ginger commonly used in herbal medicine and has antioxidant and anti-inflammatory effect on women’s health reproduction due to its flavonoid, phenolic compunds and the active antioxidant such as shagaols, gingerol, zingerone to prevent ROS buildup